Let the adventure begin: proyecto interdisciplinar en el marco de enseñanza para la comprensión (Memorias Sifored - Encuentros Educación UAN, 2021)
This document portrays the process carried out in the construction, consolidation and socialization of the interdisciplinary synthesis project called LET THE ADVENTURE BEGIN, achieved with the group of students and teachers of 5th Grade at the Colombus American School. This project, within the framework of Teaching for Comprehension (TfC), was launched by the students themselves, with the guidance of teachers in the areas of English, Social studies, Spanish, Science and Mathematics, thus consolidating a research proposal that fostered understanding from the field of virtuality, in remote access.Finally, in its nature, the project had several phases that contributed to the methodological and didactic consolidation to recognize different strategic ecosystems of our department, outline a possible tourist offer that is friendly to the environment and economically profitable; and conclude, generating the business plan or offer to the market, a product that was consolidated as a result of the analysis, systematization and understanding of the variables addressed in aforementioned problem and that was presented to the educational community in the event called Celebration of Understandings.
Keywords: Teaching for understanding; Collaborative work; Interdisciplinarity; synthesis project